Verificación funcional de un controlador de memoria para un dispositivo médico implantable. - Rodríguez-Mejía, Jean Carlo (Instituto Tecnológico de Costa Rica, 2018)
When a design is made for a product that needs to have a stable and continuous operation and also that is not expected to fail, the fucntional operation of the devices must be checked before delivering them to the end user, in this case the microprocessor designed by the Escuela de Electrónica must be ensured that the operation is almost perfect since its application as part of implantable medical devices so it can ensure life or cause the death of the user. In order to ensure the proper functioning of these devices, the Universal Verification Methodology or UVM will be used to verify the function of this device, this methodology is used by the integrated circuits design industries, it will ensure that from design stages it is possible to verify the operation of up to the last component of this microprocessor; This document focuses on memory control and the design of the environment to be able to verify it. Palabras Clave: functional verification, UVM, verification, memory controller, code coverage, functional coverage.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Verificación; UVM; Controlar; Memoria; Código; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics